Biochar affects community composition of nitrous oxide reducers in a field experiment. (April 2018) - Krause, Hans-Martin; Hüppi, Roman; Leifeld, Jens; El-Hadidi, Mohamed; Harter, Johannes; Kappler, Andreas; Hartmann, Martin; Behrens, Sebastian; Mäder, Paul; Gattinger, Andreas
Abstract: N2 O is a major greenhouse gas and the majority of anthropogenic N2 O emissions originate from agriculturally managed soils. Therefore, developing N2 O mitigation strategies is a key challenge for the agricultural sector and biochar soil treatment is one reported option. Biochar's capacity to increase soil pH and to foster activity of specialized N2 O reducers has been proposed as possible mechanisms for N2 O mitigation. An experiment was undertaken to investigate whether changes in the community composition of N2 O reducers was observed under field conditions after biochar application. The study objective was to assess the abundance and taxonomic composition of the functional marker genes nosZ and nosZ –II across a vegetation period of Zea mays L. after biochar or lime addition compared to an untreated control. After fertilization, biochar amendment resulted in a significant increase of nosZ gene copy numbers compared to the control and the lime treatment. Simultaneously a shift in community composition of nosZ-II bearing bacteria was observed in the biochar treatment that went beyond the sole liming effect. This study broadens our understanding of the functional impact of biochar on N2 O emissions and emphasizes the possibility to shape the functioning of the N2 O reducing microbial community through the addition of biochar at a field scale. Highlights: Biochar induces a shift in community composition of N2 O reducers after fertilization. Increased abundance of specialized N2 O reducers after biochar addition could be confirmed in the field. The impact of biochar on community composition of N2 O reducers is beyond the liming effect.